(untitled) (Multidisciplinary Journal of Science and Technology, 2024)
Preschool children exhibit a higher capacity for learning foreign languages compared to older children. Their educational progress heavily relies on using age-appropriate and engaging teaching methods. This article explores the role of innovative approaches, including modern technologies, short poems, and interactive activities, in fostering interest, expanding vocabulary, and enhancing pronunciation during English learning sessions.